2011
DOI: 10.1163/138577211x557567
|View full text |Cite
|
Sign up to set email alerts
|

NMRP and ATRP Double Initiators for the Formation of Binary Polymer Brushes via Grafting-From Methods

Abstract: New ATRP and NMRP initiator molecules were synthesized, which were grafted on silica wafer surfaces and served for initiating the formation of polymer brushes via the grafting-from method. Two of the new initiators bore ATRP and NMRP moieties in the same molecule. These double initiators were used to produce binary polymer brushes with switchable surface properties: styrene was first polymerized via ATRP at 40 • C and 4-vinylpyridine was polymerized thereafter at 110 • C via NMRP. The brushes achieved in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…Besides, the authors showed that polymer chains with molar masses higher than 20 000 g mol -1 were quite stretched at the surface with a cross-sectional area per chain of, in average, 200 Å 2 (i.e., corresponding to around 0.8 chains/nm 2 ). Similar linear increase of brush thichness with molar mass were reported by Devaux et al [106,112] and others [107,108,110,[113][114][115][116][117][118][119]. In the former case, the polymer brushes were prepared by NMP of styrene initiated by trialkoxysilyl-terminated alkoxyamines previously deposited on the wafer surface using the Langmuir-Blodgett (LB) technique to enable the formation of very dense brushes.…”
Section: Control Of the Surface Energy And Wetting Properties Of Func...supporting
confidence: 59%
See 3 more Smart Citations
“…Besides, the authors showed that polymer chains with molar masses higher than 20 000 g mol -1 were quite stretched at the surface with a cross-sectional area per chain of, in average, 200 Å 2 (i.e., corresponding to around 0.8 chains/nm 2 ). Similar linear increase of brush thichness with molar mass were reported by Devaux et al [106,112] and others [107,108,110,[113][114][115][116][117][118][119]. In the former case, the polymer brushes were prepared by NMP of styrene initiated by trialkoxysilyl-terminated alkoxyamines previously deposited on the wafer surface using the Langmuir-Blodgett (LB) technique to enable the formation of very dense brushes.…”
Section: Control Of the Surface Energy And Wetting Properties Of Func...supporting
confidence: 59%
“…As shown in Figure 7b, the lower the degree of chemical mistmach between the homopolymers and the grafted random copolymers, the lower was the interfacial energy (as determined from contact angle measurements), and the greater was consequently the polymer chains wetting ability. As said above, aside from this early work, the most common method for the synthesis of polymeric brushes onto flat silicon oxide surfaces is based on the use of the grafting from technique [99,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120].…”
Section: Control Of the Surface Energy And Wetting Properties Of Func...mentioning
confidence: 99%
See 2 more Smart Citations
“…[5] The first one is the addition of a graft or block copolymer. [6][7][8][9][10][11][12] To form a graft copolymer, two strategies exist, the grafting from between polymers [13][14][15][16][17][18][19][20][21] and the grafting onto, [22][23][24][25][26][27][28][29] with a polymer bearing an initiating function previously induced by ozonolysis or irradiation. [30,31] A coupling reaction through a function can also be used to generate specific functions onto a polymer chain moiety to then start a grafting from or a grafting onto.…”
Section: Introductionmentioning
confidence: 99%